Clinical Performance Measures for Adults Hospitalized With Intracerebral Hemorrhage: Performance Measures for Healthcare Professionals From the American Heart Association/American Stroke Association. Issue 7 (July 2018) - Hemphill, J. Claude; Adeoye, Opeolu M.; Alexander, David N.; Alexandrov, Anne W.; Amin-Hanjani, Sepideh; Cushman, Mary; George, Mary G.; LeRoux, Peter D.; Mayer, Stephan A.; Qureshi, Adnan I.; Saver, Jeffrey L.; Schwamm, Lee H.; et al.
Abstract : Supplemental Digital Content is available in the text.